(untitled) (NAU Journal of Technology and Vocational Education, 2025)
Agricultural education plays a crucial role in equipping graduates with the skills and knowledge needed to engage in entrepreneurial activities within the agricultural sector. However, the direct influence of agricultural education on agri-preneurial intentions may be mediated by the acquisition of specific agricultural skills and knowledge. Hence, this study investigated the role of Acquisition of Agricultural Skills and Knowledge (ASSK) as a mediator between Agricultural Education (AED) and Agri-preneurial Intentions of Graduates (APIG). A correlation research design was adopted by this study. Two hundred and sixteen (216) graduates of Agriculture and related courses were conveniently sampled for the study. Data was collected via a structured, validated, and field-tested questionnaire. The reliability of the instruments were determined using Cronbach’s alpha coefficients [AED = 0.85 α; ASSK = 0.89 α and APIG = 0.86 α]. Data collated were anonymously analyzed using frequencies, percentages, Pearson’s correlation, and linear regression. The mediation analysis indicated that AED significantly influences APIG through ASSK (β = .995, SE = .097; p < 0.05, F = 3655.043; 95% CI = [0.8049-1.1851]). More so, high positive significant associations were found between AED and APIG (r = .986; p < 0.05), AED and ASSK (r = .993; p < 0.05), and ASSK and APIG (r = .978; p < 0.05). ASSK serves as a significant mediator in the relationship between AED and APIG. This study suggests that entrepreneurial elements and experiential learning in Agricultural Education programmes in Nigeria should be enhanced by government and programme administrators to foster agri-preneurial intentions. Educational institutions and lecturers should incorporate more entrepreneurial and experiential learning elements into Agricultural Education programs.